Facilitating power development in the recovering athlete: Triple extension in rehabilitation - Lorenz, D. (Strength and Conditioning Journal, 2016)
Restoration of strength and power are vital for the recovering athlete to maximize athletic performance once the athlete returns to sport. Most high-level strength activities, such as olympic-style lifts, take place once the athlete transitions back to the weight room because these activities facilitate improvements in power. Triple extension of the ankle, knee, and hip is critical for running, jumping, and change of direction to be optimized, but many exercises in rehabilitation fail to address all 3 components. Therefore, triple extension can and should be introduced earlier in the rehabilitation process.